Uncertainty modelling and analysis of the concrete edge breakout resistance of single anchors in shear. (1st November 2020) - Olalusi, Oladimeji B.; Spyridis, Panagiotis
Highlights: Model uncertainty related to concrete breakout resistance prediction is quantified. ACI 318 and CCD displayed high bias, variability and correlations with parameters. EN 1992-4 and Grosser model displayed low bias and comparatively lower variability. Concerns stem from the observed overestimation of breakout capacity by EN 1992-4. Sensitivity of ACI 318 to edge distance is also a cause for concern. Reliability assessment is recommended. Abstract: A failed fastening element may lead to overall system collapse, significant economic loss and the loss of human life. Proper functioning and reliability of fastening elements are decisive for the overall safety performance of a structural system. Towards developing a reliability-based design model for fastening system, characterisation of the model uncertainty is imperative, since this is significant to structural performance. This paper presents the statistical characterisation of model uncertainty in four concrete breakout predictive models for single anchors in shear. The models investigated are the predictive models of widely accepted international design standards (EN 1992 and ACI 318) and analytical models from research publications (Concrete Capacity Design method (CCD) and Grosser method). The model uncertainty statistics were derived by comparing mean predicted shear breakout capacity to measured breakout capacity from the database of 366 anchor tests. ACI 318 and CCD model show high scatter and bias, with the latter model, further displaying strong correlations with shear design parameters. EN 1992-4 and Grosser analytical model portray low scatter and bias with mild correlations with shear design parameters. Overall, EN 1992-4 and Grosser models are the best predicting models of all the models considered in this study. Concerns stem from the observed general overestimation of mean shear capacity by EN 1992-4 model.